Systematic Review for Comparison Type of Pulse Tube Refrigerator - Sarah Taher Y. Al- lami, Ali A. F. Al- Hamadani (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A PTR (Pulse-Tubes-Refrigerator) is a cryocooler that could produce exceptionally low temperatures in one stage and even lower temperatures in two stages. Rather than utilizing the vapor compression cycle to achieve refrigeration, a PTR uses oscillatory compression and gas expansion within a closed space to obtain the required cooling. This paper discusses the significance of PTR and the many types of PTR. The most important feature of its primary varieties is recommended for large-scale cooling applications. Compared to Stirling pulse tube technologies, the equipment employed by GM pulse tube has been noted with low frequencies.